Lessons for the AAC field: a tribute to Dr. David Beukelman. (3rd April 2022) - Dietz, Aimee; McKelvey, Miechelle; Mirenda, Pat; Light, Janice C.; Blackstone, Sarah; Fager, Susan; Fischer, Julia; Garrett, Kathryn; Golinker, Lewis; Thiessen, Amber; Weissling, Kristy; Williams, Michael B.; et al.
Abstract: On February 5, 2022, the field of augmentative and alternative communication (AAC) lost a giant when Dr. David "Dave" Beukelman passed away. As the readership of this journal is aware, Dave was one of the principal founders of the AAC field and devoted his career to providing a voice to those without one. Before AAC became a field, people who could not talk were invisible or seldom noticed, unless they were in the way. For more than 40 years, he was a catalyst for change in AAC clinical practice, research, dissemination, teaching, and public policy development. This tribute aims to honor Dave's lifelong mission of serving others by sharing some of his most timeless and valued lessons. Each lesson begins with one of Dave's most enduring quotes that is then followed by a brief synopsis of the lesson Dave hoped to convey.